Comparing musicians and non-musicians in signal-in-noise perception. (2nd November 2019) - Zhang, Fawen; Roland, Claire; Rasul, Deema; Cahn, Steven; Liang, Chun; Valencia, Gloria
Abstract: Objectives: The objective is to compare musicians and non-musicians in signal-in-noise perception.Design: Participants underwent the following tests: (1) High-frequency (HF) audiometry, (2) QuickSIN (a test for speech perception in noise), and (3) Binaural Masking Level Difference (BMLD) test (a test that examines the hearing threshold of a low-frequency tone from noise masking when the phase of the signal or noise in one ear is reversed with respect to the phase of the signal or noise in the other ear, i.e. the difference in the threshold for detection of the tone in noise under the Sπ No and So No conditions).Study sample: Thirty-four healthy young normal-hearing listeners including 17 musicians (M) and 17 non-musicians (NM).Results: There were no study group difference in HF audiometry and QuickSIN. The M group had a significantly better performance under the So No but not under the Sπ No condition. As a result, the BMLD value (So No –Sπ No ) was significantly smaller in the M group than in the NM group.Conclusions: There is a musicians' advantage in binaural tone-in-noise detection in the BMLD task under the So No condition, suggesting that long-term music training positively shapes the auditory system.